Quality or quantity? the supply-side determinants of primary schooling in rural Mozambique - Handa, Sudhanshu; Simler, Kenneth R. (International Food Policy Research Institute, 2000)
The role of school quality in determining educational outcomes has received much research attention in the United States. However, in developing countries, where a significant part of the school age population never attends school, policymakers must consider both quality and quantity when deciding how to maximize the impact of scarce investments. Acknowledging this difference in the policy environment in developing countries, this paper provides comparative estimates of the impact of quality versus quantity investments in school supply in rural Mozambique, one of the world’s poorest countries. Policy simulations show that improving school quality (through the pupil-teacher ratio) increases grade attainment and efficiency by approximately 9 percent with no impact on overall enrollment rates. However, these same results can be generated by increasing starting enrollment probabilities through the establishment of new schools in all rural villages that currently do not have schools. Furthermore, similar rates of increase in school achievement indicators can be achieved by building schools in only 56 percent of all villages currently without schools, provided these schools are placed in those villages that also do not have a school nearby. When cost information is considered, the main policy implication is that the expansion of school quantity through well targeted placement of new schools will provide the greatest increase in educational outcomes for Mozambique at this time.